A Novel Technique for Contrast Target Detection in Through-the-Wall Radar Images - Singh A.P.; Dwivedi S.; Jain P.K. (My University, 2025)
Through-the-wall radar images suffer from strong clutter due to the presence of dielectric walls and environmental noise. Several approaches have been explored to reduce clutter for detecting targets with similar dielectric constants. However, in real-time scenarios, targets may not have similar dielectric constants. Therefore, it is necessary to develop a technique for detecting contrast targets—that is, targets with different dielectric constants behind a wall in the same scene. This paper proposes a novel technique that combines time gating and Gaussian mixture model based low-rank approximation to detect contrast targets present in the same scene. The proposed method was compared to existing clutter reduction techniques in terms of target-to-clutter ratio (TCR). The experimental results showed that the proposed approach yielded highest TCR (130.1) © Copyright The Korean Institute of Electromagnetic Engineering and Science